The effect of supervised work experience on the acquisition of employability skills among Malaysian students - Syed Sofian, Sharifah Kamaliah; Roslan, Samsilah; Bakar, Ab Rahim; Ghiami, Zeinab (Emerald, 2018)
Purpose: The vocational education and training (VET) system needs a future change in order to be more accountable to employers (and their associations) for training outcomes that match employer expectations. As part of this, an important focus is employability skills that go beyond work-related technical and interpersonal skills to include employer-preferred values, attitudes and personality dimensions. The purpose of this paper is to determine the effect of supervised work experiences (SWEs), among other factors, on undergraduate vocational trainees’ acquisition of employability skills. Design/methodology/approach: A total of 138 respondents ranging in age from 17 to 24 years who successfully completed their two years program awarded with Malaysian Skill Certificate were included. They were divided into two sub-populations, trainees participating and trainees not participating in the SWE. Descriptive analysis, Correlation and ANCOVA were applied for data analysis. Findings: The results showed that participating students achieved a moderately higher level of employability skills compared to students not participating in the SWE. The findings also revealed other factors contributing to the acquisition of employability skills, including gender, age, work experience, self-concept and achievement motivation. However, achievement motivation was found to be significantly related to the acquisition of employability skills. Therefore, participation of vocational trainees in the SWE influences the acquisition of employability skills which are identified as career success skills and could facilitate youth in transition from school to work. Research limitations/implications: Although the research has reached the aims, there were a few limitations which may effect on generalization of the findings. Because of the limit access to students from all majors in vocational training, this study focused on six types of skills. In addition, the number of participants from different courses was not equal. Practical implications: The research findings also imply several practical implications. First, based on the finding, it can be suggested that industries provide students’ vocational training under supervision of expert in their course area in order to enrich the level of trainees’ acquisition of employability skills. Second, referring to the finding, focusing on the key aspects of employability skills, industries can improve the trainees learning process and producing workers with abilities to allow them to interact with job duties in the organization of workplace. Originality/value: This study can serve as a model for evaluation when implementing school to work programs.